(untitled) (Praxis Educativa, 2022)
The present work aimed to phenomenologically categorize the organizational metaphors present in Venezuelan Higher Education Institutions. It was based on the qualitative paradigm with a phenomenological socio-historical approach, using the steps of the phenomenological method: previous, descriptive, structural and discussion of the results. In-depth, unstructured interviews were conducted with two academic vice-rectors of the Universidad del Zulia and Universidad Rafael Belloso Chacín. As a result, the presence of organizational metaphors was evidenced in the key informants’ speeches: Living organism, Evolution, Politics, Crisis, Cybernetic machine, Knowledge as power, Change, Participation, Discord and Technology as power. Finally, it was shown that the use of organizational metaphors provides a different alternative for the study of universities, thus allowing to open new schemes for their understanding and comprehension in highly complex environments.